Integrasi Sertifikasi Halal Berbasis Kearifan Lokal dalam Meningkatkan Kepercayaan Konsumen - Fatah, Muchamad Iqbal; Harizah, Siti (Moderasi : Journal of Islamic Studies, 2024)
Halal certification plays a strategic role in enhancing consumer trust in MSME products, particularly in Indonesia’s culinary sector. This study analyzes the integration of local wisdom in the halal certification process to strengthen acceptance and compliance among MSME entrepreneurs. A case study was conducted on Petis Umi Sulis, a business in Bantaran District, Probolinggo, with guidance from P3H and LPH UIN Maulana Malik Ibrahim Malang. Using a qualitative case study approach, this research employed observation, in-depth interviews, and document analysis. The findings reveal that the use of local raw materials, traditional production methods, and the application of religious values facilitate the halal certification process. Door-to-door mentoring by P3H proved effective in enhancing entrepreneurs’ understanding of halal regulations. Halal certification not only increases product competitiveness but also supports cultural preservation and community economic empowerment. Therefore, a local wisdom-based approach should be widely implemented with policy support to strengthen synergy between the government, academia, and business actors, fostering a sustainable and compliant halal business ecosystem.